Hydration of α-pinene catalyzed by acid clays - Comelli, Nora Alejandra (2013)
The hydration reaction of α-pinene in the presence of natural clays treated with monochloroacetic acid as catalyst to obtain oxygenated compounds was studied. Catalysts were characterized using X-ray diffraction, differential thermal analysis, programmed thermal desorption of adsorbed pyridine, and infrared spectroscopic analysis of adsorbed pyridine to determine Brønsted and Lewis acid sites. Catalytic tests revealed that treatment of the natural clay with the acid improved the catalytic activity and the selectivity toward oxygenated products by increasing the acidity of the catalyst. The selectivity toward oxygenated compounds increased with the augment of the α-pinene conversion because of greater contact between water molecules with the remaining α-pinene molecules. The natural clay without treatment produced compounds resulting from α-pinene isomerization, whereas the treated clays produced alcohols and other products in addition to isomerization compounds. After a certain time, the α-terpineol was isomerized into cineols. Studies of the reusability of the JAL catalyst were performed (clay treated with monochloroacetic acid). As the number of reuses increased, the percent conversion decreased; however, the selectivity toward oxygenated compounds increased.